Transformasi Sendratari Legenda Kamandaka dalam Upaya Melestarikan Kebudayaan Banyumas - Ryolita, Widya Putri; Nurhayani, Octaria Putri (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2019)
Research on the transformation of the forms ballet dance legend Kamandaka in Banyumas is one of the research focuses on the potential of local wisdom. With descriptive analytic method that is supported by the theory of transformation, This research is used to see the changing shape of the Kamandaka legend into a ballet in Banyumas. These changes are in each ballet that consists of five rounds.The first round immediately displays Kamandaka who met the gods and removed the story from the Padjajaran kingdom. Half to two figures Pulebahas king who wants to apply Ciptarasa, whereas in this story in the last parts of the story. Half to three Kamandaka contest that has changed langur unnoticed Ciptarasa, whereas in the story Ciptarasa know. The second round is the figure of Raja Pulebahas who wants to apply for Ciptarasa, while in this story there are the last parts of the story. The third round of the Kamandaka contest has changed langur without Ciptarasa knowing, while in the story Ciptarasa knows. The fourth round of the slapstick mother waistband and “prenes” Kamandaka. On waistband mother slapstick story not depicted and prenes Kamandaka occur before the contest langur. Round five the fight Kamandaka and Pulebahas be the highlight of the story, while the story is still no continuity with the royal attack Pulebahas Nusatembini belonging to Pasir Luhur. This transformation also as an entertainment alternative to the preservation of local wisdom that has potential as a tourist attraction. This transformation also as an entertainment alternative to the preservation of local wisdom that has potential as a tourist attraction.